2009
DOI: 10.1523/jneurosci.3822-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mood Influences Supraspinal Pain Processing Separately from Attention

Abstract: Studies show that inducing a positive mood or diverting attention from pain decreases pain perception. Nevertheless, induction manipulations, such as viewing interesting movies or performing mathematical tasks, often influence both emotional and attentional states. Imaging studies have examined the neural basis of psychological pain modulation, but none has explicitly separated the effects of emotion and attention. Using odors to modulate mood and shift attention from pain, we previously showed that the percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
270
5
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(296 citation statements)
references
References 65 publications
(115 reference statements)
16
270
5
2
Order By: Relevance
“…In the other study, unpleasant odors, compared with pleasant ones, increased both pain perception and activations in the ACC, medial thalamus, and primary and secondary somatosensory cortices (SI/SII) (15). However, in this case, pain-related activations were confounded with activations related to odors due to the simultaneous application of odors and painful stimulation.…”
mentioning
confidence: 77%
“…In the other study, unpleasant odors, compared with pleasant ones, increased both pain perception and activations in the ACC, medial thalamus, and primary and secondary somatosensory cortices (SI/SII) (15). However, in this case, pain-related activations were confounded with activations related to odors due to the simultaneous application of odors and painful stimulation.…”
mentioning
confidence: 77%
“…For example, the entorhinal cortex of the hippocampal formation has been shown to respond differentially to identical noxious stimuli depending on whether the perceived pain intensity was enhanced by pain-relevant anxiety [25]. Additionally, Villemure and Bushnell [26] recently reported that painrelated activity within the anterior cingulate, medial thalamus and primary and secondary somatosensory cortices was correlated with mood, whereas the effects of attentional state altered activity in anterior insular cortex. The group results from the present study therefore complement these previous studies and demonstrate details of the pain matrix including the ascending pathways, the affective components of the response and the descending modulation of the response in subcortical regions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the ventrolateral column receives convergent input from both the superficial and deep dorsal horn relaying nociceptive afferent information from visceral, muscle, and C-fiber skin nociceptors as well as visceral inputs from the nucleus of the NTS and sacral spinal cord. Functional neuroimaging studies in humans indicate that PAG activation by nociceptive inputs is modulated by attention, emotion, expectation of pain and expectation-related placebo analgesia [54][55][56][57][58][59][60][61]. Experimental studies using chemical microstimulation indicate that the different columns of the PAG organize different coping strategies to pain and other stressors [62][63][64][65][66].…”
Section: Descending Pain Modulatory Systemmentioning
confidence: 99%